PENYELESAIAN WANPRESTASI DALAM PERJANJIAN JUAL BELI TERHADAP PEMBATALAN SEPIHAK DENGAN METODE PEMBAYARAN CASH ON DELIVERY PADA PEKANBARU JUAL BELI ONLINE ELEKTRONIK DI PEKANBARU - Sarah Salsabiila; Hayatul Ismi; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
There are problems that occur in COD buying and selling transactions, one ofwhich is the occurrence of cancellations when the goods have started to be shipped orhave arrived at the buyer's place. In a transaction, the consumer unilaterally cancelsthe goods that have been ordered to the seller so that in this context the consumer hasdefaulted. For the actions of the negligent and irresponsible consumer, the seller hasclearly been harmed because he cannot get his rights and gets immaterial losses suchas the reputation of his shop which is branded bad by other consumers who read thepost.The type of legal research is sociological juridical, which in this research, iscarried out by going directly to the field to collect primary data, and using descriptivemethods. Meanwhile, if viewed from the nature of this research is descriptive.The type of legal research is juridically sociological, which in this study, iscarried out by going directly to the field to collect its primary data, and usingdescriptive methods. Meanwhile, when viewed from its nature, this research isdescriptive.The results of this study are the result of unilateral cancellations made by buyersto sellers in the PJBO Electronic Online Buying Forum, namely paying compensation tocreditors, cancellation of agreements, transfer of risk to debtors, cancellationaccompanied by payment of compensation, paying court fees if brought before thecourt. Country. The form of settlement of default in the sale and purchase agreementagainst unilateral cancellation with the Cash On Delivery payment method at the PJBOElectronic Online Buying Forum, namely the seller can file a lawsuit to the courtbecause he feels aggrieved by the consumer for the problems he experiences due to theunilateral cancellation of the consumer who uses the COD feature. However, thesethings were not done by the seller at PJBO Elektronik Pekanbaru. The seller onlyaccepts the loss caused by the buyer who unilaterally cancels the COD payment.Keywords: settlement of default, sale and purchase agreement, unilateralcancellation, COD